2019
DOI: 10.1002/ejoc.201900093
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to Diverse Libraries of Internal Alkynes via Sequential Iododediazoniation/Decarboxylative Sonogashira Reaction in Imidazolium ILs without Ligand or Additive

Abstract: Convenient access to diverse libraries of internal alkynes via decarboxylative Sonogashira reaction of alkynyl‐carboxylic acids with iodoarenes, employing imidazolium‐ILs as solvent, along with piperidine‐appended imidazolium [PAIM][NTf2] as task‐specific basic IL is demonstrated, without the need for any ligand or additive. The feasibility to perform these reactions by sequential one‐pot iododediazoniation/decarboxylative Sonogashira reaction is also shown, and the scope of the methods is underscored by provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Accordingly, the Sonogashira reactions were also successfully performed in conventional ionic liquids such as [BMIM][PF 6 ] [2225], [BMIM][BF 4 ] [23], [HMIM][BF 4 ] [24], [EMIM][NTf 2 ] [26], [nBuPy][X] (X = PF 6 – , BF 4 – , NO 3 – ) [27], [DectBu 3 P][BF 4 ] [28]. It was found that some of these systems could operate copper-free [25,27,29] and/or auxiliary base-free conditions [30]. Recently, some “designer" ionic liquids were also developed for this purpose [2933] from which an imidazolium-based piperidine-appended one could act as task specific compound operating either as a solvent in itself [31] or as an additive to the common ionic liquids [30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the Sonogashira reactions were also successfully performed in conventional ionic liquids such as [BMIM][PF 6 ] [2225], [BMIM][BF 4 ] [23], [HMIM][BF 4 ] [24], [EMIM][NTf 2 ] [26], [nBuPy][X] (X = PF 6 – , BF 4 – , NO 3 – ) [27], [DectBu 3 P][BF 4 ] [28]. It was found that some of these systems could operate copper-free [25,27,29] and/or auxiliary base-free conditions [30]. Recently, some “designer" ionic liquids were also developed for this purpose [2933] from which an imidazolium-based piperidine-appended one could act as task specific compound operating either as a solvent in itself [31] or as an additive to the common ionic liquids [30,33].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that some of these systems could operate copper-free [25,27,29] and/or auxiliary base-free conditions [30]. Recently, some “designer" ionic liquids were also developed for this purpose [2933] from which an imidazolium-based piperidine-appended one could act as task specific compound operating either as a solvent in itself [31] or as an additive to the common ionic liquids [30,33]. It should be noted; however, significant catalyst loadings (5–10 mol %) were necessary to obtain reasonable product yields for latter reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions were also performed in sequence, by one-pot iododediazoniation/decarboxylative Sonogashira coupling, leading to diverse libraries of internal alkynes (Scheme 5 ). 15…”
Section: Aryldiazonium Salts and Aryltriazenes As Coupling Partners I...mentioning
confidence: 99%
“…Thus, in an endeavor to overcome these limitations, a greener synthetic protocol towards the access of the target molecule is conceived by the use of ionic liquids as a reaction medium/promoter mainly due to its environmental acceptability. In our long pursuit of developing sustainability and greener strategies, we have established green synthetic methodologies employing ionic liquids as solvent or catalyst for the synthesis of benzoxazole and benzothiazoles and metal‐mediated cross‐coupling reactions exploiting 1‐aryltriazenes as a coupling partner. With these previous knowledge, we report herein the base/ligand free and open‐air Pd/Cu catalyzed arylation of azoles at C2 position with three different 1‐aryltriazenes as coupling partner instead of a single triazene reagent that reported elsewhere …”
Section: 3‐diethyl‐1‐(phenyl)‐triaz‐1‐ene As a Coupling Partner Formentioning
confidence: 99%